Best practices for designing and planning events where human-animal interactions are encouraged, based on observations of risk behaviors and hand hygiene at such events - Erdozain, Gonzalo (Kansas State University, 2013)
Outbreaks of human illness have been linked to visiting settings with animal contact throughout developed countries. These outbreaks demonstrate that although contact with animals in public settings can provide educational and entertainment opportunities, the potential to spread disease exists if risk-reduction tools are not implemented, proper hygiene measures aren’t practiced, and precautions are not taken and reinforced. This thesis is divided into two parts. Part one is an observational study of hand hygiene tool availability and recommendations; frequency of risky behavior; and, handwashing attempts by visitors in Kansas and Missouri, U.S., petting zoos. Part two delineates best practices for organizing events where human-animal interactions are encouraged, in hopes it will lower the risk of zoonotic disease transmission. Handwashing signs and hand hygiene stations were available at the exit of animal-contact areas in 10/13 and 8/13 petting zoos respectively. Risky behaviors were observed being performed at all petting zoos by at least one visitor. Frequently observed behaviors were: children (10/13 petting zoos) and adults (9/13 petting zoos) touching hands to face within animal-contact areas; animals licking children’s and adults’ hands (7/13 and 4/13 petting zoos, respectively); and children and adults drinking within animal-contact areas (5/13 petting zoos each). Of 574 visitors observed for hand hygiene when exiting animal-contact areas, 37% (n=214) of individuals attempted some type of hand hygiene, with male adults, female adults, and children attempting at similar rates (32%, 40%, and 37% respectively). Visitors performed hand hygiene more often when a staff member was present within or at the exit to the animal-contact area (136/231, 59%) than when no staff member was present (78/343, 23%; P < 0.001, OR = 4.863, 95% CI = 3.380–6.998), and in petting zoos where animal contact occurred over a fence (188/460, 40.9%) as opposed to visitors entering an animals’ yard for contact (26/114, 22.8%; P < 0.001, OR = 2.339, 95% CI = 1.454–3.763). Inconsistencies existed in tool availability, signage, and supervision of animal- contact. Risk communication was poor, with few petting zoos outlining risks associated with animal-contact, or providing recommendations for precautions to be taken to reduce these risks. Recommendations made in the second part of this thesis were based on these observations, recent publications, and the suggestions of many health agencies. It focuses on what event planners can do to design and plan a safer event, and what staff working at the event should be aware of in order to inform visitors and lower the risk of zoonotic disease transmission. Part two discusses two primary tools to reduce risk of zoonotic disease transmission: sanitation and awareness of risk behaviors. Keeping facilities, animals, and visitors clean, and informing visitors of risky behaviors to avoid, while reinforcing positive messages within the animal- contact area, can lower the risk of zoonotic infection. Included with the second part, is a checklist (see appendix A) designed for visitors to assess whether an event that encourages human-animal interaction poses a high or low risk. By identifying possible risk factors, teachers and parents will be able to make an informed decision about the safety of the human-animal encounter.
Keywords: Petting zoo; Zoonotic disease; Handwashing; Risky behaviors; Hand hygiene; Design; Public Health (0573); Veterinary Medicine (0778)